PENGENDALIAN GULMA AIR MELALUI PEMANFATAN IKAN KOAN (Ctenopharyngodon idella ) DI DANAU LIMBOTO - Lamondo, Djuna (Jurnal Sainstek, 2008)
Koan fish is the one of fish herbivore that can use the plant as their food in high number. The eating ability of the fish influenced by the gut structure of the koan fish. The koan fish have a short gut and this cause the digesting ability is uncompleted. For balancing, the koan fish needs the high number of plant for their food. The ability of koan fish in eating plant is influenced by the age and the weight of fish. The study by Onu (2007) in limboto lakes shows that the one year of koan fish with 250 fish per net can eat 1.12 kg/m2 of Euchornia (eceng gondok). This more effectives than five month of koan fish that can eat Euchornia (eceng gondok) only 0.46 kg/m2. Other factor also influences the ability of koan fish in eating water plan. The population density, kind of species, and weed location in the water also can influence the ability of fish in eating the weeds. Koan fish can be live in water with the oxygen content about 0.41 to 28 mg/l, pH 5.0 to 9.0 and temperature 0 to 33o C. Koan fish can be reproduce in the temperature 30.4o C. Based on data, it knows that oxygen content of Limboto lakes is about 1.73 to 9.84 mg/l and pH about 7 8.5. Limboto Lake temperature is about 25.0 to 32.9 o C with the average is 29.75 o C. If we see the ability of koan fish to eat the water plant and considering to lives prerequisite of koan fish life so the koan fish can be used as weed control in Limboto Lake.